MACHINE VISION BASED COIN SEPERATOR AND COUNTER - RAM, B.SURESH; BABU, P.MAHESH; KIRAN, K.RAVI; SAGARIKA; SWATHI, V. (The journal of contemporary issues in business and government, 2022)
Automation holds a vital role in nearly all walks of the human life. Separation and counting of Indian currency coins is considered in this project. Nearly all the temples in India have donation boxes (Hundi). More human intervention is required to separate such coins and hence it could be automated and as a result it improves efficiency and reduces the time consumption in the process. This project adapts automation for this time-taking process. It involves the usage of digital image processing technology that aids in detecting the coins and differentiating them thus, making the process faster and more accurate.